Blind versus Fluoroscopy-guided Percutaneous Nephrolithotomy: A Randomized Clinical Trial - Karami, Hossein; Mazloomfard, Mohammad Mohsen; Moeini, Aida; Mohammadhosseini, Mojtaba; Rezaei, Alireza; Lotfi, Behzad (Urology Journal, 2014)
<!--[if gte mso 9]> 800x600 <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:Arial;} --> <!--[endif] --> Purpose: Due to the negative impact of radiation on the patient and the surgical team during percutaneous nephrolithotomy (PCNL), we aimed to evaluate success rate and complications of blind access for PCNL using lumbar notch landmark and compare with conventional fluoroscopy- guided access. Materials and Methods: In a clinical trial, 100 patients who were candidate for PCNL, were randomly assigned into blind group (1) and fluoroscopy-guided group (2). In group 1 the lumbar notch was used to guide percutaneous access and in group 2 fluoroscopy performed after needle insertion, Amplatz placement and at the end of surgery. If the access failed, we would repeat puncturing up to 5 times. In group 2, access was achieved using full fluoroscopy guidance. All patients underwent postoperative assessment including kidney-ureter-bladder X-ray and ultrasonography. Results: Both mean access time and mean operation time were statically similar in group 1 and group 2 (3.3 ± 0.5 vs. 3.6 ± 0.7 min and 35.2 ± 4.6 vs. 38.9 ± 4.1 min, respectively). A successful puncture was achieved in 86% and 94% of the patients in groups 1 and 2, respectively (P = .18). Total success rate of procedure was 80% and 88% of the patients in groups 1 and 2, respectively (P = .27). Conclusion: According to this study, it seems that blind access is a safe and effective PCNL method, and we recommend employment of this technique by skilled endourologist in urology centers especially for patient with large hydronephrotic kidney.